Food security and restrictions of trading in agricultural real estate in the context of the “Farm to Fork” Strategy - Wojciechowski, Paweł (Przegląd Prawa Rolnego, 2021)
The aim of the considerations was an attempt to outline the mutual relations between restrictions of trading in agricultural real estate introduced by the Act on shaping the agricultural system, food security and sustainable food systems, as well as to verify to what extent Polish regulations concerning the agricultural real estate may be perceived as an instrument to ensure food security and whether the legal solutions adopted are consistent with the “Farm to Fork” Strategy. The article presents the basic goals and assumptions of the “Farm to Fork” Strategy, taking into account the European Green Deal, explains the concept of food security, and outlines the basic instruments for restrictions of trading in agricultural real estate introduced by the Act on shaping the agricultural system. In the light of these findings, an assessment of the introduced solutions restricted trading in agricultural real estate in the context of food security and the “Farm to Fork” Strategy was made. The analysis carried out in the article leads to the conclusion that both the principle of purchasing agricultural real estate by individual farmers and the requirement to run a farm on the purchased agricultural real estate contribute to ensuring food security, but they only indirectly affect the implementation of the “Farm to Fork” Strategy.